Introducing holmium laser enucleation of the prostate alongside transurethral resection of the prostate improves outcomes of each procedure - Wilson, N (Royal College of Surgeons, 2013)
INTRODUCTION: Holmium laser enucleation of the prostate (HoLEP) is recognised as an alternative to transurethral resection of the prostate (TURP). HoLEP has been demonstrated to be at least as effective as TURP with less morbidity but its introduction to practice has been limited in part by the learning curve of a novel procedure. This study examined the effects of introducing HoLEP alongside an established practice of TURP on early morbidity and length of hospital stay (LOS). METHODS: A retrospective review of all patients who underwent HoLEP and TURP between April 2007 and July 2011 was undertaken. HoLEP was introduced in April 2008; patients undergoing TURP before this were considered as a historical control group. Data were collected concerning resection/enucleation weight, blood transfusions and LOS. RESULTS: Overall, 772 patients underwent HoLEP or TURP within the 52-month study period: 164 underwent TURP prior to the introduction of HoLEP (TURP-A), 425 had TURP after the introduction of HoLEP (TURP-B) and 183 underwent HoLEP. The mean removed weight was 24g (standard deviation [SD]: 21g) for TURP-A, 19g for TURP-B (SD: 16g) and 38g (SD: 32g) for HoLEP (p<0.005). Blood transfusion rates were 5.5%, 2.2% and 1.6% for the TURP-A, TURP-B and HoLEP groups respectively (p<0.05). For TURP-A patients, the mean LOS was 5.6 days (SD: 3.5 days, 95% confidence interval [CI]: 5.3–6.0 days). The mean LOS for TURP-B patients was 4.4 days (SD: 4.4 days, 95% CI: 4.2–4.8 days). HoLEP patients had a mean LOS of 3.0 days (SD: 3.0 days, 95% CI: 2.6–3.4 days). CONCLUSIONS: The introduction of HoLEP alongside TURP is associated with lower rates of blood transfusion and shorter LOS for all patients. This is likely to be due to the use of HoLEP rather than TURP in patients with larger prostates, who are more likely to have complications.